Systematic network-based discovery of a Fam20C inhibitor (FL-1607) with apoptosis modulation in triple-negative breast cancer. Issue 7 (26th April 2016) - Qin, Ziyi; Wang, Peiqi; Li, Xinyi; Zhang, Shouyue; Tian, Mao; Dai, Yi; Fu, Leilei
Abstract : Family with sequence similarity 20, member C (Fam20C) is a physiological Golgi casein kinase that phosphorylates multiple secreted proteins. Abstract : Family with sequence similarity 20, member C (Fam20C) is a physiological Golgi casein kinase that phosphorylates multiple secreted proteins. Recently, it has been reported that Fam20C can be identified as a novel kinase target for therapeutic development. Thus, inhibition of Fam20C will be a potential therapeutic strategy to prevent tumor cell progression and metastasis. In our study, based upon the systems-biology network, molecular modeling and molecular dynamics (MD) simulations, we discovered a novel Fam20C inhibitor (FL-1607) with potent anti-proliferative effects on triple-negative breast cancer (TNBC) cells. Subsequently, we found that this Fam20C inhibitor could induce apoptosis and inhibit cell migration in MDA-MB-468 cells. Together, these findings would provide a new clue to the exploration of more novel Fam20C inhibitors for future TNBC therapy.